A1.10 The GM-CSF/CCL17 axis in the rheumatoid synovial environment. (24th February 2016) - Kidger, SV; Ellson, CD; McInnes, IB; Sleeman, MA; Robinson, MJ; Goodyear, CS
Abstract : Background and objectives: GM-CSF is a pivotal growth factor/cytokine that can drive aspects of RAimmunopathogenesis. In particular, GM-CSF can activate monocytes and induce their differentiation towards alternative phenotypes. The synovial environment also contains additional factors that can influence monocyte activation such as damage associated molecular patterns (DAMPs); many of which signal via TLR4. However, the impact of GM-CSF on monocytes in a synovial setting is not well understood and therefore we aimed to investigate the response of monocytes to GM-CSF in the context of synovial fluid (SF) co-stimulation. Materials and methods: Monocytes isolated from human blood or murine bone marrow were cultured in the presence or absence of GM-CSF (1ng/ml) and co-stimulated with SF (2.5%/5%) from RA or OA patients. Supernatants were harvested after 24 h and chemokine and cytokine secretion was analysed by ELISA and/or MSD. Immune complexes were made by incubating human IgG and Staphylococcal Protein A at a ratio of 4:2 respectively. Results: Monocytes from healthy individuals and RA patients, secreted substantial amounts of CCL17 upon stimulation with GM-CSF. In healthy monocytes, GM-CSF driven induction of CCL17 was significantly inhibited (P < 0.01) upon co-stimulation with RA-SF but not OA-SF, whilstthe expression of other chemokines and cytokines was un-affected. GM-CSF induced phosphorylation of STAT5 was not affected by RA-SF exposure, suggesting the inhibition was downstream of receptor and proximal signalling. Furthermore, inhibition of CCL17-induction via RA-SF was TLR-independent, as RA-SF could inhibit CCL17 induction in MyD88/TRIF double knockout murine monocytes. In addition to DAMPs, SF also contains immune complexesand cytokines. We tested if TNF, IL1a or IL-6 could reproduce the effect of SF, but none of these cytokines impacted GM-CSF induction of CCL17. To investigate if the inhibitory capacity of SF may be due to immune complexes, small immune complexes were made, and these did inhibit GM-CSF-mediated production of CCL17 in monocytes. Conclusions: GM-CSF induced production of CCL17 in monocytes is inhibited by RA-SF. The underlying mechanism is not known, however, our work shows that it is TLR-independent and downstream of STAT5 phosphorylation. Immune complexes also inhibit GM-CSF induction of CCL17 suggesting these may contribute to the phenomenon.